Problems of the chidren’s traumatism: structure, dynamics of types during the long-time follow-up - Mikhalchuk, V. N.; Bondar, S. O. (Journal of Education, Health and Sport, 2017)
There are presented the results of studying the structure of children’s traumatism, dynamics of its variable types during 1999 –2016 inUkraineand Kirovogradska Oblast. The peculiarities by the character of changes in indices and their intensity with years were defined.